The Case of THE CASE: A Future Summary of Jonglian Poetry, Using Fictional Devices (Journal of the Association for the Study of Australian Literature, 2011)
The article is a ficto-critical piece that imagines an Australian poetry that has been influenced by the innovative Diary of Chinese gold-miner Jong Ah Sing. The Diary was written 1866-72 and is held by the State Library of Victoria. The stylistic devices, such as capital letters and unorthodox syntax, as well as references to invented punctuation, all derive from this manuscript which is one of the texts I am examining for my PhD thesis.